PEM fuel cells theory and practice - Barbir, Frano, 1954- (Academic Press, 2013)
Demand for fuel cell technology is growing rapidly. Fuel cells are being commercialized to provide power to buildings like hospitals and schools, to replace batteries in portable electronic devices, and as replacements for internal combustion engines in vehicles. PEM (Proton Exchange Membrane) fuel cells are lighter, smaller, and more efficient than other types of fuel cell. As a result, over 80% of fuel cells being produced today are PEM cells. This new edition of Dr. Barbir's groundbreaking book still lays the groundwork for engineers, technicians and students better than any other.